УЧАСТИЕ СПЕЦИАЛИСТОВ ПРИ РАССЛЕДОВАНИИ МОШЕННИЧЕСКИХ ДЕЙСТВИЙ С КРЕДИТНЫМИ РЕСУРСАМИ - Moldazym, N. (Journal of actual problems of jurisprudence, 2019)
In clause the opportunities of attraction of the experts for the decision of tasks of investigation of swindle with credit and financial resources are considered (examined).